Covid-19 and public health. (1st June 2021) - Pollock, Allyson M.; Harding-Edgar, Louisa
Abstract : The UK has the highest death rate from Covid-19 in the world, and it is vulnerable groups who have suffered the most. This article describes the multiple failures of government that led to this tragedy. The depletion of and disinvestment in public health services, communicable disease control and community health services over decades meant those reliant on these services were failed. The fundamental tenets of public health were set aside, and public health expertise ignored, in favour of establishing a parallel, privatised system for epidemic control which failed expensively and spectacularly. Long-established principles of infectious disease control and rules and standards for scientific evaluation were not followed, and our 'world-class scientists' fatally departed from World Health Organisation advice. Covid has been used as a cover for more privatisation and less scrutiny and accountability. It has exposed the gap between rich and poor and erosion in our public services. However, rather than ameliorating inequalities, the government has presided over enormous inter- and intra-generational transfers of harms and risks from rich to poor and to those in institutional settings, and from older prosperous people to children. Above all, Covid has been a cover for enormous transfers of wealth from the public purse and public services to private interests — notably in health services. There is a political solution to the undermining of public health, commercial conflicts and lack of public accountability: the government must bring forward legislation to reinstate a publicly funded, publicly operated and fully integrated National Health and Care Service, and set out clear plans for reinvestment and restoring and rebuilding health and care services.